Analisis Impelementasi Project Penguatan Profil Pelajar Pancasila ( P5 ) Melalui Model Pembelajaran Project Based Learning ( Pjbl ) Dalam Upaya Meningkatkan Kecintaan Siswa Terhadap Lingkungan Di SDIT Wasilatul Huda - Nina; Ecep Romdoni (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to analyze the implementation of the project to strengthen the profile of Pancasila students (P5) through the project based learning (PjBL) learning model and efforts to increase students' love of the environment at SDIT Wasilatul Huda. The research method used is a qualitative approach with descriptive research type. Data collection techniques use observation, interviews and documentation. This research is based on a lack of understanding of P5 or the Project for Strengthening the Pancasila Student Profile so that it is implemented with the Project Based Learning learning model as well as the lack of awareness of students regarding the school environment which can be seen by scattered rubbish, scribbles on tables and walls and so on. From the existing population, class IV SDIT Wasilatul Huda sampling was taken. The results of the research were in the form of descriptions of the students' condition before the research and after the research, namely in the form of students' level of awareness of cleanliness before the research which was very poor and even tended not to know the importance of cleanliness. After conducting student research, especially the creation of a waste recycling project, the level of awareness of cleanliness increased, thereby creating a clean and pleasant environment.